Unusual presentation of uterine rupture following laparoscopic myomectomy: a case report and literature review - Cheong, Cassandra P. S.; Tan, Andy W.K.; Tan, Lay Kok; Yu, Su Ling (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Laparoscopic myomectomy is preferred to the laparotomy approach as the former promises a better postoperative course, with fewer complications and faster recovery. It is increasingly performed in younger women in recent years. However, although rare, uterine rupture is an important and dangerous complication. Authors report a case of 36-year-old lady who presented at 23 weeks and 4 days gestation of an in vitro fertilization (IVF) dichorionic diamniotic twin pregnancy with spontaneous uterine rupture. She underwent a laparoscopic myomectomy three year prior for a 4.5cm fundal fibroid. Her presenting symptoms include acute onset of epigastric pain. Uterine rupture was confirmed using Computed Tomography scan. She underwent an exploratory laparotomy and the placenta was found extruding from a 4cm defect on the posterior fundus along the previous myomectomy scar with active bleeding. Current literature suggests it is difficult to predict when uterine rupture may happen. Proper selection criteria for suitable cases may allow trial of labour after myomectomy to be a viable option. Potential considerations include interval between myomectomy and conception, scar integrity, method of repair, and the use of electrocoagulation. This case reports the worrying features of an early antepartum rupture presenting with atypical symptomatology. In pregnant patients presenting with abdominal pain or haemodynamic instability, it is imperative to consider uterine rupture so as to perform timely intervention. Those with a history of laparoscopic myomectomy should be considered high risk and counseled about the risk of rupture with extensive discussion about mode of delivery.